ANALISIS PEMBENTUKAN TANAH DARI BATUAN PENUTUP OVERBURDEN PADA AREA REKLAMASI PT BORNEO INDOBARA GUNA MENDUKUNG KEBERHASILAN REKLAMASI SECARA BERKELANJUTAN - Yudha Hadiyanto Eka Saputra; Suyanto Suyanto; Fatmawati Fatmawati; Suhaili Asmawi (Universitas Lambung Mangkurat, 2022)
This study aims to analyze the process of soil formation on overburden material in the reclamation area in 2013 (9 years), 2015 (7 years), and 2018 (4 years) to support the success of sustainable reclamation, and analyze the relationship between planting age, morphology and climate conditions in the study area that can affect the process of soil formation in the overburden. The research was conducted at a coal mining company located in Tanah Bumbu Regency, South Kalimantan Province. The research method used was descriptive quantitative. Data collection was done by making a test trench and taking soil profile data which includes topsoil thickness, intermediate layer, and overburden. Soil texture, soil color, and data on roots that penetrated the soil were also recorded and analyzed. The results of the test trench analysis showed that the process of soil formation in the overburden began to occur in the reclamation area in the 9th year (2013). The indicator found lateral roots in the soil layer at a depth of 40-60 cm which is an overburden layer with gray soil color. The correlation test showed a strong relationship between soil acidity (pH) and the year of planting (r2 = 0,74). The relationship between organic C elements and the year of planting (r2 = 0,68). The element N in the soil has a very strong relationship with the year of planting (r2 = 0,92). The next element was P2O5 in the soil having a moderate relationship (r2 = 0,46) and K2O elements had a strong relationship (r2 = 0,75). The results of soil chemical analysis and also soil texture showed that the soil fertility status at the study site was in low condition. This study concluded that the process of soil formation in overburden was found in the planting year area of 2013 or year 9, with indicators such as the appearance of roots in the overburden area at a depth of 20 - 40 cm, whereas in 2015 and 2018 no roots were found in the overburden. Climatic and morphological conditions accelerated the process of soil formation in the overburden because this very wet condition accelerated the process of leaching nutrients to the surface layer of the reclamation area. The process of weathering in the soil, especially in overburden, will cause plant roots to enter the overburden layer by bringing nutrients produced by trees, undergrowth, and litter to the research area.